Energo-Mechanical Evaluation of Damage Growth and Fracture Initiation in Aviation Composite Structures. (23rd July 2016) - Keršienė, Neringa; Raslavičius, Laurencas; Keršys, Arturas; Kažys, Rymantas; Žukauskas, Egidijus
ABSTRACT: The aim of the present paper is to (1) highlight the results of laboratory damage detection and monitoring in the aviation composite materials, during a mechanical testing constituted of multiple loadings, and (2) obtain a detailed understanding of damage evolution of composite specimens with regard to impact energy. Woven 12-ply glass fiber and 16-ply carbon fiber–reinforced epoxy composites (GFRP 92 125/L285/287 and CFRP 98 131/L285/287) were used as less studied subjects in research. This study explored the resistance to cracking and delamination of glass and carbon fiber laminates with the same resin system under low-load conditions. GRAPHICAL ABSTRACT: